Implicit Bias in Health Care Providers During Providing Health Care Services to Patients in A Tertiary Care Hospital South Punjab Pakistan - Leghari, Shazia Yasmeen; Perveen, Tahira; Nazar, Kalsoom (Future Science, 2023)
Introduction: Bias means an unreasoned and unfair distortion of judgment in favour of or against a person or thing. It is the evaluation of something or someone that can be positive or negative, and implicit or unconscious bias is when the person is unaware of their evaluation. Unconscious or implicit bias describes associations or attitudes that reflexively alter our perceptions, there by affecting behaviour, interaction, and decision-making Methods: This study qualitative cross-sectional study design is used. Implicit Assessment Tool (IAT) used to assess the age Implicit, Religion Implicit and Skin tone Implicit among nurses. The data was analysed by SPSS version-18 & Microsoft Excel. Out of 100 respondent 23% showed a strong automatic preference for light skin compared to dark skin people in Skin-tone IAT. Results: Out 0f 100 just 2% showed strong automatic preference for dark skin as compared to light skin people. During the Religion IAT out of 100 respondents just 1% nurses showed a strong preference for Judaism compared to Islam. 96.0% showed strong automatic preferences for Islam compared to Judaism. 29 % respondents showed a strong automatic preference for Islam compared to Christianity. While 2% participants showed a strong preference for Christianity compared to Islam. In Age implicit assessment test 30% nurses showed strong automatic preference for young people to old people. Just 1 % nurses showed strong automatic preference for old people compared to young people. 30 % nurses showed moderate level of automatic preferences for young people as compared to old people, while just 2 % have moderate automatic preference for old people as compared to young people. Conclusion: This study concluded that Nurses have a strong automatic preference towards their own religion so that they prefer Muslim patients unconsciously rather than the other religion. This study also reveal that during giving care nurses have strong automatic preference to young people and light skinned people as compared to dark skinned and old people.